Development of an Unconventional Method to Control the Ectoparasites in Backyard Poultry - Shanta, I. S.; Begum, N.; Majumder, S.; aman, Anisuzz; Karim, M. J. (Biological Sciences - PJSIR, 2008)
Dust of Nicotiana tabacum, Azadirachta indica and Polygonum hydropiper when applied in the poultry sheds as bedding for control of six species of lice, one species of fly and two species of mites, highest efficacy (96.67%) was shown by tobacco at 15% concentration followed by neem at the same concentration (efficacy, 77.52%) and tobacco at 10% concentration. Tobacco at 15% concentration significantly (p<0.05) reduced the ectoparasitic burden within 12 days with maximum mean body weight gain by poultry, being 232.30 g.